PEDAGOGICAL IMPLICATION OF THE RHETORICAL STRUCTURES OF BARACK OBAMA'S AND HILLARY CLINTON'S DEBATES DURING DEMOCRATIC CAMPAIGN PERIOD OF AMERICAN PRESIDENTIAL ELECTION IN 2008 - Slamet Utama (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
This study discusses the rhetoricalfeatures ofBarack Obama's and Hillary Clinton's debates. This debate was carried out during the Democratic campaign period on American presidential election in 2008. The main focus of this dissertation is on the examination of the patterns of Communicative purposes or 'moves' and their subsequent elements or 'steps' of the arguments. The analysis includes the examination of communicative purposes and persuasive values of the texts, and linguistic features used to materialise the communicative purposes and persuasive values. The problem statements of the study are: 1/ What are the rhetorical features realized in Barack Obama's and Hillary Clinton's debates during Campaign Period on American Presidential Election in 2008?, 21 From the rhetoricalfeatures perspective, how can Barack Obama's and Hillary Clinton's debates attract the audience?, 3/ Pedagogically, what lessons can language learners obtain from the debate between Obama and Hillary Clinton? This study found that macro rhetorical structure of the debate (ie. Initiation, Response, and Feedback) is relatively similar to that of a common debate except that, unlike in common debate, the Initiation is given by moderators and questioners, the Responses given by debaters, and Feedback can be given by moderator, questioner, or debaters. In this debate, there is no interruption while the debater was speaking. The debater would speak only if he/she was given an opportunity to speak. And the other difference from the common debate is that Barack Obama's and Hillary Clinton's debates had already been designed by the Dream Team before the debate occured. However, the communicative purposes and persuasions in the debates are relatively the same. The debaters persuade the audience to give them votes in the American presidential election in 2008. The differences are found in the way that rhetorical devicess use linguistic resources to realize the communicative purposes and persuations in the arguments. The rhetorical differences are caused by the differences in the arguments of offering the approaches to solve the Americans' problems. The pedagogical implication of this study is that the debate genre needs to be explicitly taught to Indonesian students, especially university students in order to give them more acces to the content of debate, and to develop skills needed by Indonesian lecturers. For this purpose, an appropriate approach needs to be developed; that is to teach the generic features of debate such as in speaking.